A full-spectrum solar chemical energy storage system with photochemical process and thermochemical process. (October 2018) - Fang, Juan; Liu, Qibin; Guo, Shaopeng; Lei, Jing
Abstract: A solar chemical energy storage system with photochemical process and thermochemical process is proposed to convert full-spectrum solar energy into chemical energy. The ultraviolet and part of visible sunlight are firstly absorbed by norbornadiene derivatives, and the norbornadiene derivatives are converted into the related quadricyclane derivatives. When the quadricyclane derivatives are catalyzed, they are converted back to the norbornadiene derivatives for next cycle. The storage and releasing cycle are eco-friendly without CO2 emission. The rest of solar energy, which cannot be used in the solar photochemical process, are exploited by solar thermochemical process, providing heat for methanol decomposition. It is demonstrated that solar photochemical efficiency increases firstly and then it decreases with the increase of cut-off wavelength, while the solar thermochemical efficiency declines with the cut-off wavelength rising. In the hybrid system, the decrease of the solar thermochemical efficiency is balanced by an increase of the solar photochemical efficiency, and the maximum solar-to-chemical efficiency of the hybrid system reaches 68.7%.